Gender challenges in family farming: Have they been overcome? (Desenvolvimento em Questão, 2026)
The study presents gender issues on small rural properties. This qualitative, study was to identify and discuss the challenges and potential of women in family farming, based on Feminist Theory and the dimensions of the FIRO Theory. Eighteen women were interviewed, and primary data were analyzed using content analysis. The interviews revealed 104 obstacles, with lack of income, gender devaluation, and difficult working conditions as the most salient issues. This study provides insights into the gender-based challenges faced by women in family farming and proposes sustainable interventions to address them. It was possible to understand how women relate to other family members, considering their position in businesses.
Keywords: Family farming; Woman challenges; Decision-making process; Gender issues; Rural women